State Housing Management in Interface Areas: Reflections on Access to Land, Housing and a Dignified Habitat - Blanco Avila, Ana María (2025)
In San Juan, Argentina, the beginning of the new millennium was marked by a strong state territorial intervention mainly linked to the development of housing policies that defined the use and distribution of urban land, and the access to basic goods and services by its population. The article reflects on the regularization policies of the southwest interface of the San Juan Metropolitan Area in the last two decades, in the framework of the state housing relocation processes developed, and their relevance in the access to housing and land, as well as in the construction of democratic and sustainable territories that ensure social and environmental justice to their inhabitants. In this context, we ask: what were the characteristics of these public policies, were there differences between the policies of the beginning of the century and those of the last decade, and what were the social implications of these processes? The methodological strategy involved the adoption of a largely qualitative perspective that combined documentary, conversational and observational techniques. The main finding relates to the housing policies implemented and the resulting improvements in access to land and housing for the most vulnerable sectors, despite persistent deficiencies in access to decent housing.